Review of recent progress in nanoscratch testing. (1st June 2013) - Beake, B D; Harris, A J; Liskiewicz, T W
<x xml:space="preserve">Abstract</x> Nanoscratch testing, as an important technique for the assessment of the mechanical failure behaviour and adhesion strength of ceramic coatings and a simulation tool of single asperity contact in tribological experiments, is increasingly becoming an established nanomechanical characterisation method. This paper reviews recent work in nanoscratch testing in different engineering applications including thin ceramic films, automotive organic coatings, chemical-mechanical polishing and biomaterials. In the main part of the paper, nanoscratch results from experiments performed using NanoTest systems fitted with tangential force sensors and spherical indenters as scratch probes are presented and discussed. The types of nanoscratch tests described include constant load nanoscratches, ramped load nanoscratch tests and multipass repetitive unidirectional constant load nanoscratch tests (nanowear). The results are discussed in terms of critical load sensitivity to intrinsic and extrinsic factors, impact of scan speed and loading rate, influence of probe radius and geometry, estimation of tip contact pressure, influence of surface roughness and film stress and thickness, and finally role of ploughing on friction evolution.